TG13 current terminology, etiology, and epidemiology of acute cholangitis and cholecystitis. Issue 1 (January 2013) - Kimura, Yasutoshi; Takada, Tadahiro; Strasberg, Steven M.; Pitt, Henry A.; Gouma, Dirk J.; Garden, O. James; Büchler, Markus W.; Windsor, John A.; Mayumi, Toshihiko; Yoshida, Masahiro; Miura, Fumihiko; Higuchi, Ryota; et al.
Abstract While referring to the evidence adopted in the Tokyo Guidelines 2007 (TG07) as well as subsequently obtained evidence, further discussion took place on terminology, etiology, and epidemiological data. In particular, new findings have accumulated on the occurrence of symptoms in patients with gallstones, frequency of severe cholecystitis and cholangitis, onset of cholecystitis and cholangitis after endoscopic retrograde cholangiopancreatography and medications, mortality rate, and recurrence rate. The primary etiology of acute cholangitis/cholecystitis is the presence of stones. Next to stones, the most significant etiology of acute cholangitis is benign/malignant stenosis of the biliary tract. On the other hand, there is another type of acute cholecystitis, acute acalculous cholecystitis, in which stones are not involved as causative factors. Risk factors for acute acalculous cholecystitis include surgery, trauma, burn, and parenteral nutrition. After 2000, the mortality rate of acute cholangitis has been about 10 %, while that of acute cholecystitis has generally been less than 1 %. After the publication of TG07, diagnostic criteria and severity assessment criteria were standardized, and the distribution of cases according to severity and comparison of clinical data among target populations have become more subjective. The concept of healthcare‐associated infections is important in the current treatment of infection. The treatment of acute cholangitis and cholecystitis substantially differs from that of community‐acquired infections. Cholangitis and cholecystitis as healthcare‐associated infections are clearly described in the updated Tokyo Guidelines (TG13).